Enhancing advance encryption standard security based on dual dynamic XOR table and MixColumns transformation - Adnan Ibrahem Salih; Ashwaq Mahmood Alabaichi; Ammar Yaseen Tuama (Institute of Advanced Engineering and Science, 2020)
An efficient approach to secure information is critically needed at present. Cryptography remains the best approach to achieve security. On this basis, the national institute of standards and technology (NIST) selected Rijndael, which is a symmetric block cipher, as the advanced encryption standard (AES). The MixColumns transformation of this cipher is the most important function within the linear unit and the major source of diffusion. Dynamic MixColumns transformation can be used to enhance the AES security. In this study, a method to enhance the AES security is developed on the basis of two methods. The first method is an extension of a previous study entitled “A novel Approach for Enhancing Security of Advance Encryption Standard using Private XOR Table and 3D chaotic regarding to Software quality Factor.” In the current study, the fixed XOR operation in AES rounds is replaced with a dual dynamic XOR table by using a 3D chaotic map. The dual dynamic XOR table is based on 4 bits; one is used for even rounds, and the other is used for odd rounds. The second method is dynamic MixColumns transformation, where the maximum distance separable (MDS) matrix of the MixColumns transformation, which is fixed and public in every round, is changed with a dynamic MDS matrix, which is private, by using a 3D chaotic map. A 3D chaotic map is used to generate secret keys. These replacements enhance the AES security, particularly the resistance against attacks. Diehard and NIST tests, entropy, correlation coefficient, and histogram are used for security analysis of the proposed method. C++ is used to implement the proposed and original algorithms. MATLAB and LINX are used for the security analysis. Results show that the proposed method is better than the original AES.